Micronutrient status of intensively cultivated potato growing soils of Jalandhar district - Kumar, Sushil (Potato Journal, 2017)
Available Zn, Fe, Mn, Cu and boron were studied in 100 farmers in the intensively cultivated soils (potato based and non-potato based cropping systems) in Jalandhar district of Punjab. A large variation was observed in DTPA extractable zinc ranging from 0.20 to 9.76 ppm (mean 3.20), Fe ranging from 1.61 to 180.9 ppm (mean 44.9), Cu ranging from 0.4 to 4.55 ppm (mean 2.18) ppm and Mn ranging from 1.74 to 141.0 ppm (mean 36.9).Majority of the soils contained high to very high contents of micronutrient cations. Based on critical limits of 0.55, 4.5, 0.3 and 1.0 mg/kg soil for Zn, Fe, Cu and Mn, respectively, out of 100 only one sample was found deficient in zinc and eight samples were marginally deficient in Fe. Hot water extractable boron was less than 0.5 ppm in all the soils. As per the soil fertility evaluation and fertilizer recommendations in the state 49% samples were low and 49 %were medium in soil organic carbon. Micronutrient content (Zn, Fe, Cu and Mn) in soils of potato based cropping system was higher than soils of non-potato based cropping system. Available Zn, Fe, Cu and Mn contents were higher in soils where paddy was being grown and available Fe, Mn and Zn contents were 4.72, 1.46 and 1.52 times higher in soils where paddy was a component crop of the cropping system compared to the soils where paddy was not being grown.